Politik Asik: Upaya Edukasi Politik menggunakan Media Board Game - Mustofa, Mustabsyirotul Ummah; Utama, Rafif Sakti; Paskarina, Caroline; Rahmatunnisa, Mudiyati; Herdiansah, Ari Ganjar (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: The fast development of technology demands adjustments in political education. The